Deprotonation of Coordinated Phosphanes in a Rhenium Complex: CC Coupling with Diimine Coligands. Issue 9 (21st January 2015) - Arévalo, Rebeca; Pérez, Julio; Riera, Lucía
Abstract The reaction of fac‐[Re(bipy)(CO)3(PMe3)][OTf] (bipy=2, 2′‐bipyridine) with KN(SiMe3)2 affords two neutral products: cis, trans‐[Re(bipy)(CO)2(CN)(PMe3)], and a thermally unstable compound, which features a new CC bond between a P‐bonded methylene group (from methyl group deprotonation) and the C6 position of bipy. The solid‐state structures of more stable 1, 2‐bis[(2, 6‐diisopropylphenyl)imino]acenaphthene analogs, resulting from the deprotonation of PMe3, PPhMe2, and PPh2Me ligands, are determined by X‐ray diffraction.